2016
DOI: 10.5935/1678-9741.20160007
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity inspiratory protocol increases heart rate variability in myocardial revascularization patients

Abstract: Objective:To evaluate heart rate variability during an inspiratory muscle endurance protocol at three different load levels [30%, 60% and 80% of maximal inspiratory pressure], in patients who had previously undergone coronary artery bypass grafting.Methods:Nineteen late postoperative myocardial revascularization patients participating in a cardiovascular rehabilitation program were studied. Maximal inspiratory pressure maneuvers were performed. An inspiratory muscle endurance protocol at 30%, 60% and 80% of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…26 These findings, taken together, may indicate that ventilatory muscle relief, or even ventilatory muscle training, which aims to increase the strength of these muscles, may minimize the effects of intolerance to physical exercise in cardiac surgery patients during the postoperative period, 27 given that this procedure is closely associated with important losses in pulmonary function. 28 Although the 2 protocols presented in this study showed benefits to subjects, the intervention group protocol delivered additional improvements, mainly in the primary outcome variable. This shows that the interventions during the physical therapy sessions have clinical applicability and important functional outcomes that decrease the length of hospital stay, thus resulting in a reduction of the total hospital cost, even for short hospital stays.…”
Section: Eligible Patients 59mentioning
confidence: 78%
“…26 These findings, taken together, may indicate that ventilatory muscle relief, or even ventilatory muscle training, which aims to increase the strength of these muscles, may minimize the effects of intolerance to physical exercise in cardiac surgery patients during the postoperative period, 27 given that this procedure is closely associated with important losses in pulmonary function. 28 Although the 2 protocols presented in this study showed benefits to subjects, the intervention group protocol delivered additional improvements, mainly in the primary outcome variable. This shows that the interventions during the physical therapy sessions have clinical applicability and important functional outcomes that decrease the length of hospital stay, thus resulting in a reduction of the total hospital cost, even for short hospital stays.…”
Section: Eligible Patients 59mentioning
confidence: 78%
“…IMT has the function of enabling muscles to perform their functions more easily, increasing strength and endurance, promoting improved inspiratory muscle fatigue, dyspnoea, and ventilatory capacity, and consequently improving quality of life (Aznar‐Lain et al, ; Watsford & Murphy, ). There is evidence in the literature that IMT in different diseases can also improve thoracoabdominal mobility, increase the distance walking in the 6MWT, decrease dyspnoea during physical effort (Basso‐Vanelli et al, ) and improve cardiac autonomic function (Caruso et al, ; Mello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The level of significance will be 5%. The effect size will be calculated using Cohen's d, and the results will be interpreted based on Cohen (1988) (Caruso et al, 2016;Mello et al, 2012).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Some degree of pulmonary impairment is unavoidable in the immediate postoperative period following CABG. 5 These effects may persist, resulting in 25-30% reductions in lung volume, 6 maximal inspiratory and expiratory pressure (MIP and MEP) relative to expected values), 7 and thoracic mobility. 8 The patient has a sternotomy and is then connected to a cardiorespiratory bypass machine during coronary artery bypass grafting (CABG), the usual treatment for CAD.…”
Section: Introductionmentioning
confidence: 99%